Results of field studies on the strength switch type R65 brand 1/9 project 65109 W-01 - Orlovskyi, A. M.; Hnatenko, V. P.; Moiseienko, K. V. (Science and Transport Progress, 2010)
The results of full-scale test of the strength of the switch type R65, mark 1/9 of the design 65109Zh-01 are presented.